Empowerment of healthy lifestyles for the Sungai Lumbah village community during the COVID-19 pandemic - Akhmad Syakir Syakir (Borneo Community Development, 2021)
In addition to equipping the public with knowledge about Covid-19, it is also necessary to provide knowledge about the important keys to avoiding transmission/transmission of the Covid-19 virus, namely knowledge about health and a clean and healthy lifestyle (PHBS). So we need to do community service in Sungai Lumbah village, Alalak district, Barito Kuala Regency, South Kalimantan related to healthy lifestyles during the covid-19 pandemic. The method used is using the method of observation, interviews, socialization, and counseling or education. The result of this activity is that the community, in this case the children and our mothers, educates them about getting to know fruits, vegetables and herbal drinks that can be used as food for children's growth and to keep the immune system strong.